YAP/TAZ: Drivers of Tumor Growth, Metastasis, and Resistance to Therapy - Thompson, Barry J. (BioEssays, 2020)
The transcriptional co‐activators YAP (or YAP1) and TAZ (or WWTR1) are frequently activated during the growth and progression of many solid tumors, including lung, colorectal, breast, pancreatic, and liver carcinomas as well as melanoma and glioma. YAP/TAZ bind to TEAD‐family co‐activators to drive cancer cell survival, proliferation, invasive migration, and metastasis. YAP/TAZ activation may also confer resistance to chemotherapy, radiotherapy, or immunotherapy. YAP‐TEAD cooperates with the RAS‐induced AP‐1 (FOS/JUN) transcription factor to drive tumor growth and cooperates with MRTF‐SRF to promote activation of cancer‐associated fibroblasts, matrix stiffening, and metastasis. The key upstream repressor of YAP/TAZ activation is the Hippo (MST1/2‐LATS1/2) pathway and the key upstream activators are mechanically induced Integrin‐SRC and E‐cadherin‐AJUBA/TRIP6/LIMD1, growth factor induced PI3K‐AKT, and inflammation‐induced G‐protein coupled receptor (GPCR) signals, all of which antagonize the Hippo pathway. In this review, strategies to target YAP/TAZ activity in cancer are discussed along with the prospects for synergy with established pillars of cancer therapy. YAP and TAZ are key mediators of wound healing and tissue regeneration responses as well as important drivers of solid tumor growth, metastasis, and resistance to therapy, making them attractive therapeutic targets for cancer.